Inkjet printing Ag-TiO2 thin films with suppressed photoluminescence. (23rd September 2019) - Fang, Mei; Liu, Fang; Li, Tianli; Zhang, Wenchao; Xia, Huayan; Rao, K V; Belova, Lyubov
Abstract: With ultraviolet sensitive photochemistry and photoelectric properties, TiO2 is attractive for applications like photocatalysis, photovoltaic devices, and sunscreen products, among others. By coating Ag on TiO2 surface, the sensitivity can be extended to visible light, endowing enhanced properties with potential new applications. In this work we inkjet print Ag-TiO2 films from particle suspensions, and investigate the structure, morphology, Ag distribution and the photoluminescence of the films. It is found that Ag nanoparticles form bridges among TiO2 particles during the post-annealing. These metallic bridges can transport the excited electrons and suppress the recombination of electrons and holes with the photoluminescence of the film reduced by more than half. The work provides an industrial applicable, low-cost, environment friendly route of preparing Ag-TiO2 films for attractive photochemistry and photoelectric device applications.